Josep Palau i Fabre: l'home és un animal que es busca - Manuel Guerrero Brullet (Catalonia)
The intense and short relation with Antonin Artaud undeniably marked the first years of Josep Palau i Fabre's stay in Paris: a dangerous alchemical initiation, tending towards madness. This article explores Le livre Artaud, a novel project preserved by the Fundació Palau, and certain texts dedicated to Picasso. It explores the meanings behind the Palau's motto «l’home és un animal que es busca» presented in Doble assaig sobre Picasso (1964), which is the key interpretation of Palau's work.